Love Speaking Understanding: Possible Steps toward Greater Church Unity Regarding Tongues through Biblical Theology - Christian Ramsey (Religions, 2023)
Paul’s address regarding spiritual gifts in 1 Corinthians 12 and 14 is conspicuously centered around his address of love in chapter 13. It could appear Paul is emphasizing that love is to be at the center of the exercise of spiritual gifts. If that is the case, one question in the context of Global Pentecostalism seems to be “How does love intersect with the gift of tongues in community and why does it matter?” In our day of political and social division, Jesus persists in his desire for Church unity. In the context of this Special Issue, the investigation herein proposes suggestions grounded in biblical theology for adjustments in the expectations of the manifestation of tongues and the practice of tongues in the local assembly. The expression of tongues, for various reasons, is a point of contention within the body of Christ. Addressed here are the questions of a requirement of God to manifest tongues, and the legitimacy of exercise of uninterpreted tongues in the assembly. This study hopes to add to the conversation in revisiting a biblical theology for both.